Barriers to self-administered home-based task-oriented practice post-stroke: development and content validity of a new instrument - Nascimento J.R.T.* (2024)
© 2023 Informa UK Limited, trading as Taylor & Francis Group.Purpose: To develop a new instrument to identify barriers to self-administered home-based task-oriented practice post-stroke and test its content validity. Materials and methods: The sample consisted of individuals with stroke and neurological rehabilitation professionals. The study consisted of two steps: (1) Instrument development, involving three processes; a data search in the literature, interviews with the target population and an open questionnaire (online) sent to professionals; and (2) Testing the content validity of the instrument by asking individuals with stroke and professionals about the comprehensiveness and relevance of the items and additionally asking individuals with stroke about the comprehensibility of the items. For each item in the instrument, the threshold validity scores were ≥0.80 in the Content Validity Index and ≥0.75 for the Kappa agreement. Results: The preliminary version was developed with 46 items. The content validation was performed in three rounds. The last version of the instrument Barriers to self-administered home-based task-oriented practice post-stroke (BASH-TOP-Stroke) contained 34 items in five response categories, in which the higher the value presented, the greater the number of barriers. The content validity for the items was excellent. Conclusions: The study provides a new instrument to help identify barriers to self-administered home-based task-oriented practice post-stroke.